Impact of Revenue Generating Systems and Performance in Local Authorities in Zimbabwe: a Case of Chiredzi Town Council - Chanyau, Tatenda (Midlands State University, 2017)
Revenue generation is the nucleus and bedrock for sound local authority sustainability. Thus this research examines the impact of income generating systems and performance at Chiredzi Town council. This is because local authorities as the third tier of government and closest to the people need revenue to provide basic social services to the citizens. However it is unfortunate that Chiredzi Town Council is failing to generate the much needed revenue despite the fact that the local authority collect revenue from existing sources of revenue due to factors influencing revenue generating system. The researcher used both primary and secondary methods of data collection to generate the needed information. Information obtained through questionnaires were presented in graphs, tables and expressed in percentages. Study findings indicate that the following factors hinder revenue generation in local authorities: political interference, mismanagement of income generating projects, inability to collect fully revenue due and limited powers to make by-laws among others. The researcher therefore recommended strategies for effectively maximising revenue generation and alternative sources of revenue.